The Development of AXL Inhibitors in Lung Cancer: Recent Progress and Challenges - Sang, Yun Beom; Kim, Joo-Hang; Kim, Chang-Gon; Hong, Min Hee; Kim, Hye Ryun; Cho, Byoung Chul; Lim, Sun Min (Frontiers in Oncology, 2022)
AXL, along with MER and TYRO3, is a receptor tyrosine kinase from the TAM family. Although AXL itself is not thought to be a potent oncogenic driver, overexpression of AXL is known to trigger tumor cell growth, survival, invasion, metastasis, angiogenesis, epithelial to mesenchymal transition, and immune suppression. Overexpression of AXL is associated with therapy resistance and poor prognosis. Therefore, it is being studied as a marker of prognosis in cancer treatment or as a target in various cancer types. Recently, many preclinical and clinical studies on agents with various mechanisms targeting AXL have been actively conducted. They include small molecule inhibitors, monoclonal antibodies, and antibody-drug conjugates. This article reviewed the fundamental role of AXL in solid tumors, and the development in research of AXL inhibitors in recent years. Emphasis was placed on the function of AXL in acquired therapy resistance in patients with non small cell lung cancer (NSCLC). Since clinical needs increase in NSCLC patients with acquired resistance after initial therapy, recent research efforts have focused on a combination treatment with AXL inhibitors and tyrosine kinase inhibitors or immunotherapy to overcome resistance. Lastly, we deal with challenges and limitations encountered in the development of AXL inhibitors.